Report: proposed upgrading to the existing interior design of Nasi Lemak Ayam Kampung Restaurant at No 43,45 Jalan Ali Pitchay, Ipoh, Perak for Nasi Lemak Ayam Kampung Restaurant/ Engku Ahmad Aziz Engku Zainal - Engku Zainal, Engku Ahmad Aziz (Faculty of Architecture, Planning and Surveying, 2012)
This article is focus to interior design students on how to present plan,develop and understanding about interior design. All the knowledge from semester one till semester five will be put to the test by self proposing a final project based on a real life factors such as the project itself, the client, the site and the budget.The chosen project will then go through several analysis and design process before finally confirming the final design.The choosen project must have general issues and design issues related to them in order for it to be a visible project. In this, the project report i have proposed upgrading interior design of Nasi Lemak Ayam kampung at No, 43, 45, Jalan Ali Pitchay, Ipoh, Perak.